Fertility potential in adult men treated for uncorrected bilateral cryptorchidism: A systematic literature review and analysis of case reports. (8th January 2021) - Muncey, Wade; Dutta, Rahul; Terlecki, Ryan P.; Woo, Lynn L.; Scarberry, Kyle
Abstract: Objective: Reports of adult orchidopexy for bilateral undescended testicles (bUDT) are sparse, and fertility outcomes are not well established. Our aim was to determine prognosis for restoration of spermatogenesis among adult men (≥18 years) undergoing orchidopexy for bUDT. Methods: A systematic literature review, conforming to the PRISMA statement, was conducted using the PubMed/MEDLINE and EMBASE databases through March 2020 using search terms "adult" AND "bilateral orchidopexy" OR "bilateral cryptorchidism." Relevant referenced articles from non‐indexed journal were identified by Google Scholar search and additionally included. Results: Fifty‐seven publications including adult men with uncorrected bilateral UDTs were identified. Baseline semen analysis was reported in 157 men, all of whom demonstrated azoospermia. Testosterone values were reported in 82 cases and were normal in 89%. Germ cells could not be identified in 72.6% of histologic specimens from 62 testicles. Abdominal testicles more frequently lacked germ cells (90%, p = 0.038) on univariate analysis. Eleven cases identified ejaculated spermatozoa following adult bilateral orchidopexy (8 publications). Sperm extraction (TESE) during orchidopexy or orchiectomy was reported in 13 men without success. Delayed TESE (median 10 months) was performed in 22 persistently azoospermic men with success in 10 (45.5%), none of whom had abdominal testicles prior to orchidopexy. Six men experienced successful paternity via natural conception (3) or assisted reproduction (3). Conclusion: Fertility is possible in adult men with inguinal bUDT following orchidopexy. Subsequent sperm retrieval may involve ejaculated specimens or delayed TESE. TESE performed prior to or at time of orchidopexy is unlikely to be of benefit.